Analyzing the impact of synergistic environmental regulations and local government competition on carbon neutrality goals - Jun Zhao; Lelai Shi (Journal of Innovation & Knowledge (JIK), 2025)
Integration and synergy of environmental policies is crucial for maximizing carbon reduction effects. This study investigates the heterogeneous impact of environmental policy synergy on carbon neutrality using panel data from 30 Chinese provinces between 2003 and 2022 and employing generalized quantile regression and spatial econometric models. The relevant findings are threefold. (1) The marginal impact of environmental policy synergy on per capita carbon emissions exhibits distinct structural characteristics across different positions in the conditional distribution of China's per capita carbon emissions. (2) Significant heterogeneity is evident in the effects of various environmental policy synergy categories on carbon neutrality. Specifically, synergies between government and enterprise environmental regulation (ER), and government-and public-type ER effectively reduces per capita carbon emissions, contributing to carbon neutrality. In contrast, the synergy between enterprise and public-type ER policies increases per capita carbon emissions, while the synergy between all three types of ER policies does not significantly impact carbon emissions. (3) The direct effect of local government competition on per capita carbon emissions is negligible; however, government and corporate policy synergy results in increased per capita carbon emissions under government competition. This study reveals the heterogeneous effects of policy combinations, providing a dynamic decision-making basis for optimizing policy instruments in achieving carbon peaking and carbon neutrality.
Keywords: Q54; Q58; H77; C23; D62; O18; 650; Environmental regulation; Policy synergy; Carbon neutrality; Local government competition; Generalized quantile regression; Spatial econometric regression